ETIKA KOMUNIKASI DAN TOLERANSI DALAM MENCIPTAKAN KEHARMONISAN HIDUP BERMASYARAKAT - Ahmad Bukhori (CV. Adiba Aisha Amira, 2025)
Effective communication in building social harmony is essential to create unity. Building harmony in society requires serious efforts starting from each individual or family as the smallest organisation in society that has duties, roles, and as an initial educational process in instilling values of tolerance from an early age, as well as activities in the community that can encourage mutual respect for differences, maintain harmony and unity, sharing, belonging, tolerance, and a strong desire to live in peace. As a diverse nation, diversity and differences are inevitable in society, but with good communication and a shared determination, a peaceful, just, prosperous and harmonious life can be created, as desired by all levels of society. A society is said to live in harmony if the interactions or relationships between individuals or groups in society run well, have a sense of solidarity, respect differences, feel mutual need, build cooperation, help each other, and so on.